The mediating role of flourishing on religious faith and psychological distress: a pilot survey - Chen, Joanna Chiang-Yu (Mental health, religion & culture, 2023)
Flourishing is a growing topic in positive psychology, and the positive influences of flourishing have been well documented. Although recent literature has shown that religion has an impact on one’s physical and psychological well-being in positive ways, the relationship between religiosity and flourishing has surprisingly not been studied. The present study aimed to explore the relationship of religious faith with flourishing and psychological distress. An online survey has successfully recruited 267 participants from UK and Taiwan. The survey used standardised inventories including the PERMA Profiler, the Santa Clara Strength of Religious Faith Questionnaire, and the Clinical Outcome in Routine Evaluation to measure flourishing, religious faith and psychological distress respectively. Results show that participants with strong religious faith do have higher levels of flourishing. Yet Path Analysis shows that participants who have stronger religious faith is indirectly related to lower psychological distress through the mediating effect of flourishing. Suggestions for future research and implications of the findings are discussed.